Physiologically Based Pharmacokinetic Modeling to Understand the Absorption of Risperidone Orodispersible Film - Chen, Fang; Liu, Hongrui; Wang, Bing; Yang, Liuliu; Cai, Weimin; Jiao, Zheng; Yang, Zhou; Chen, Yusheng; Quan, Yingjun; Xiang, Xiaoqiang; Wang, Hao (Frontiers in Pharmacology, 2020)
Objective: The aim of the present study was to investigate the absorption routes as well as the potential application of the oral transmucosal delivery of risperidone orodispersible film (ODF) using physiologically based pharmacokinetic modeling. Methods: The pharmacokinetic study after intragastric (i.g.), supralingual, and sublingual administration of risperidone ODF was conducted in Beagle dogs. Then a mechanic absorption model which combined Oral Cavity Compartment Absorption and Transit (OCCAT) model with Advanced Compartment Absorption and Transit (ACAT) model for predicting the absorption routes of risperidone ODF in vivo was constructed using GastroPlusTM. A sensitivity analysis was performed to investigate the impact of oral residence time on the in vivo absorption of risperidone ODF. Based on the fraction of intraoral absorption, the potential of the oral transmucosal delivery of risperidone were predicted. Results: There were no statistical differences in the AUC0–t (P = 0.4327), AUC0-∞ (P= 0.3278), Cmax (P=0.0531), and Tmax (P = 0.2775) values among i.g., supralingual, and sublingual administration of risperidone ODF in Beagle dogs. The predicted absorption percentage via oral mucosa at oral residence time of 2 min, 5 min, and 10 min was 7.0%, 11.4%, and 19.5%, respectively. No obvious difference was observed for the bioavailability of risperidone ODF within 10 min of oral residence time. The PBPK absorption model for risperidone could be simplified to include ACAT model solely. Conclusion: The main absorption route for risperidone ODF was the gastrointestine. The absorption percentage via oral mucosa was almost negligible due to the physicochemical properties of risperidone although ODF dissolved completely in the oral cavity of Beagle dogs within 2 minutes.